Zmeny v bezpečnostných systémoch STK - Bernát, Rastislav; Záležák, Zoltán; Beneš, Libor; Luptáková, Natália (Univerzita Pardubice, 2012)
The Inspection facility must meet the requirements specified in the laws and regulations of the Slovak Republic as well as in the requirements of European Union legislation. All of the necessary the criteria is very difficult to reconcile. Problems have been created in the operation and directly affect the customer.The given paper is closely connected with security of system for the collection and protection of information to verify technical condition of vehicles in use. Innovative changes are directly related the organization of work in the workplace, the quality and credibility of information collection. We observed a change in the administrative formalities of introducing multilevel control of the Inspection facility, which will be entry into force of the law in the near future.
Changes in the security systems of the inspection facility
Keywords: innovative changes of the inspection facility; quality collection of information; control elements; bar codes